(untitled) (Malaysian Management Journal, 2002)
Performance can be regarded as almost any behavior, which is directed toward task or goal accomplishment. Despite extensive research, discussion and debate on how to predict employees’ performance, teachers performance is complex and remains difficult to predict and evaluate. Teachers are still uncertain whether they can rely on some specific characteristics of performance. In view of this practice and in evaluating teachers ’performance at the work place, it is therefore the interest of the researcher to conduct a study on secondary school teachers, so as to determine their job motivation and job performance. The second objective of this study is to compare job motivation with job performance and the third one is to compare teaching performance with job performance of secondary school teachers. This correlation study involved a total of 245 secondary school teachers throughout Kedah. Data will be analyzed using the t-test and ANOVA.